Squirrel cage induction motor scalar control constant V/F analysis - K. A. M. Annuar; M. R. Sapiee; Rozilawati M. Nor; M. S. M. Azali; M. B. N. Shah; Sahazati Md. Rozali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In constant V/f control technique it is assume that the stator resistance and leakage inductance drops are negligible, especially at high speed and small load. In other words, the back emf is comparatively large at high speed and hence these voltage drops can be neglected. By maintaining constant V/f, constant Eg/f and hence constant air-gap flux is assumed. This assumption is however invalid at low speeds since a significant voltage drop appears across the stator impedance. The terminal voltage, V no longer approximates  ag. By using MATLAB Simulink, the open-loop constant V/f is simulated. It is shown that the performance of the drive deteriorates at low speeds. The improvement in the performance by applying voltage boost is shown and discussed.